2020
DOI: 10.1186/s13229-020-00378-7
|View full text |Cite
|
Sign up to set email alerts
|

Autistic traits, systemising, empathising, and theory of mind in transgender and non-binary adults

Abstract: Background Prior research examining autistic traits in gender minority adults has reported mixed findings. Most prior studies did not include non-binary individuals. Little is known about the mechanisms shaping autistic traits in gender minority adults. This study examined autistic traits, as well as constructs related to the extreme male brain theory of autism and the mindblindness theory, in transgender and non-binary adults. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Additionally, it enables comparability with other studies and facilitates application in clinical settings. The binary coding of sex/gender information may be regarded conventional as it neglects persons with differing sexual identity and personal self-concept potentially influencing socio-cognitive functioning (e.g., Kung, 2020 ). Thus, standard scores provided here may not be applicable in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it enables comparability with other studies and facilitates application in clinical settings. The binary coding of sex/gender information may be regarded conventional as it neglects persons with differing sexual identity and personal self-concept potentially influencing socio-cognitive functioning (e.g., Kung, 2020 ). Thus, standard scores provided here may not be applicable in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Di Ceglie et al ( 2014 ) then reported that empathizing in adolescent transgender males and transgender females was lower than that of cisgender females, though they did not find any differences for systemizing. Although findings in this area have been equivocal (for a review, see van der Miesen et al, 2016 ), Stagg and Vincent ( 2019 ) and Kung ( 2020 ) recently confirmed the pattern of findings that would be predicted by the EMB theory: in both studies, lower empathizing and higher systemizing were found in transgender males relative to cisgender females, but no significant differences were found between transgender females and cisgender males. Although Warrier et al ( 2020 ) reported lower empathizing and higher systemizing in transgender and gender-diverse individuals compared with cisgender individuals in a very large sample, no analysis by birth-assigned sex was possible in that study.…”
Section: Introductionmentioning
confidence: 84%
“…These findings are consistent with observations of an increased prevalence of autism diagnosis (Heylens et al, 2018 ) and elevated levels of autistic traits in adults attending gender clinics (Heylens et al, 2018 ; Jones et al, 2012 ; Pasterski et al, 2014 ), although it should be noted that not all studies have observed such effects (e.g., Vermaat et al, 2018 ; see also Nobili et al, 2018 ). Warrier et al ( 2020 ) also showed that transgender and gender-diverse adults scored higher on a self-report measure of autistic traits, and other researchers have reported elevated levels of autistic traits in adults with self-reported gender diversity (Kristensen & Broome, 2015 ; Kung, 2020 ). Other studies have indicated that autistic adults report elevated rates of gender variance (Cooper et al, 2018 ; George & Stokes, 2018 ) as well as an elevated likelihood of desiring to be a different gender to that assigned at birth (van der Miesen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…ASD is more commonly diagnosed in males (3:1 male:female ratio, according to current estimates), although there seems to be a high likelihood of a gender bias in the diagnosis of ASD [ 32 ]. According to the extreme male brain theory, autistic traits in general ASD populations would represent an exaggerated version of the psychological profile typically observed in male individuals and would be associated with increased prenatal exposure to sexual steroids that impact prenatal brain development [ 33 , 34 , 35 , 36 ]. This theory is supported by the known role of sex hormones in brain organization and function during developmental periods, in addition to their activation role in adults [ 37 ].…”
Section: Discussionmentioning
confidence: 99%